Adalimumab Effectiveness Up to Six Years in Adalimumab-naïve Patients with Crohn's Disease: Results of the PYRAMID Registry. Issue 9 (8th February 2019) - Loftus, Edward V; Reinisch, Walter; Panaccione, Remo; Berg, Sofie; Alperovich, Gabriela; Bereswill, Mareike; Kalabic, Jasmina; Petersson, Joel; Thakkar, Roopal; Robinson, Anne M; D'Haens, Geert
Abstract: Background: PYRAMID was an international multicenter, noninterventional, postmarketing registry assessing long-term safety and effectiveness of adalimumab (Humira), as used in routine clinical practice. Methods: Adult patients with moderately to severely active Crohn's disease with or without prior adalimumab experience were enrolled in the registry and followed for up to 6 years. Effectiveness measurements included the Physician's Global Assessment (PGA, a composite of Harvey Bradshaw Index [HBI] and rectal bleeding score), clinical remission (HBI < 5), Short Inflammatory Bowel Disease Questionnaire (SIBDQ), and Work Productivity and Activity Impairment (WPAI) questionnaire. Data were reported for adalimumab-naïve patients and analyzed by baseline immunomodulator use and disease duration. Results: This study evaluated 2057 adalimumab-naïve patients. Mean PGA improved from 7.5 (baseline) to 3.9 (year 1) and 3.3 (year 6). The proportion of patients in HBI remission increased from 29% (573 of 1969; baseline) to 68% (900 of 1331; year 1) and 75% (625 of 831; year 6). Patients stratified by baseline immunomodulator use had similar HBI remission rates; patients with disease duration <2 years achieved numerically higher HBI remission rates than patients with longer disease duration. Patient-reported SIBDQ and WPAI scores improved at year 1; all WPAI subscore improvements were clinically meaningful (≥7% point change) at year 1 and maintained through year 6. Serious infections were reported in 11.1% of patients; incidence rates of malignancies, lymphoma, and demyelinating disorders were low. Conclusion: Adalimumab therapy, as used in routine clinical practice, improved physician-reported and patient-reported disease outcomes and remission rates for up to 6 years. No new safety signals were observed. Abstract : Long-term effectiveness and safety of adalimumab were evaluated in routine clinical practice settings in patients with Crohn's disease. Adalimumab improved disease activity, work productivity, and activity impairment in adalimumabnaïve patients enrolled in PYRAMID registry. No new safety signals were identified.